The struggle to govern the snow crab (Chionoecetes opilio) in the Barents Sea - Jentoft, Anna Reibo (UiT The Arctic University of Norway, 2018)
This thesis is dedicated to study the main challenges that occurs when a new resource is to be made manageable, in accordance with the Norwegian principles of fisheries management and international obligations and agreements. The research object of this thesis is the snow crab (Chionoecetes opilio), and its current establishment in the Barents Sea. The study is based on theory of governability and interactive governance. In order to assess the snow crab fishery, and to identify the most pressing conflicts and those factors that are decelerating the degree of governability, an analysis of the fishery was conducted based on a governability assessment matrix. The assessment showed that the most intricate conflicts involved international agreements on utilization in the Svalbard area and disagreements on the current status of the snow crab as a sedentary species.